Cylindrical Three-Dimensional Millimeter-Wave Imaging via Compressive Sensing. (1st October 2015) - Zhao, Guoqiang; Li, Shiyong; Ren, Bailing; Qiu, Qingwei; Sun, Houjun
Abstract : Millimeter-wave (MMW) imaging techniques have been used for the detection of concealed weapons and contraband carried by personnel. However, the future application of the new technology may be limited by its large number of antennas. In order to reduce the complexity of the hardware, a novel MMW imaging method based on compressive sensing (CS) is proposed in this paper. The MMW images can be reconstructed from the significantly undersampled backscattered data via the CS approach. Thus the number of antennas and the cost of system can be further reduced than those based on the traditional imaging methods that obey the Nyquist sampling theorem. The effectiveness of the proposed method is validated by numerical simulations as well as by real measured data of objects.